Modeling of a hybrid externally fired gas turbine applied to a landfill and green waste management facility. (15th September 2021) - Mirandola, Saverio; Pedrazzi, Simone; Allesina, Giulio; Muscio, Alberto
Graphical abstract: Highlights: Biomass to power conversion was simulated using an hybrid EFGT cycle. A hybrid cycle was applied to a landfill to exploit green waste and landfill gas. Landfill gas combustion increased the TIT boosting the cycle efficiency. 17.89% of overall electrical efficiency was reached by the hybrid EFGT cycle. The economic analysis showed a PBT of 5.5 years and a NPV value of about 6.7 M€. Abstract: This work discusses the integration of an externally-fired-gas-turbine power plant in a waste disposal facility where municipal solid waste is disposed in a landfill while green waste is pre-treated and selected to be sold as fuel for biomass power plants. The advantages deriving from the in situ green waste biomass conversion using the externally-fired-gas-turbine power plant is simulated using a thermodynamic model implemented in Matlab Simulink. Two different configurations are simulated: a Standard-Externally-Fired-Gas-Turbine (S-EFGT) power plant fuelled with green-waste-derived wood chips and a Hybrid-Externally-Fired-Gas-Turbine (H-EFGT) power plant fuelled with the previous biomass together with landfill gas. Power plant subsystems are modelled through a black box approach. Inputs and outputs of each box are interconnected together to create the overall models. Preliminary simulations were performed for each configuration at the same working fluid flow rate to compare the electrical and thermal efficiency of both power plants. Full scale simulations, considering an existing case study, are then developed. First, energy fluxes and the resulting efficiencies of each configuration are evaluated. Then the techno-economical comparison between the proposed solutions is discussed. Results show a net electrical energy production of 9392 MWh/year with an electrical efficiency of 14.03% for the S-EFGT using about 18, 294 ton/year of wood biomass; the H-EFGT energy yield is 25, 392 MWh/year with an electrical efficiency of 17.89% using the same biomass consumption and an average flow rate of 1200 Nm 3 /h of landfill gas. The economic analysis is completed considering the wood biomass sale, the Net Present Value (NPV) analysis showed a payback time of 7 years for the S-EFGT investment and 5.5 years for the H-EFGT one, the NPV value is 1.310.600, 00 € and 6.655.792, 00 € for the S-EFGT and H-EFGT configuration, respectively.